Synthesis and Characterization of Electrode with Pd-Ni/C Catalyst and Performance Test of MEA for Applications in Proton Exchange Membrane Fuel Cell (PEMFC) - Yulianti, Dwi Hawa; Dedi Rohendi,; Edy Herianto Majlan,; Addy Rachmat,; Dilla Nursyahfitri,; Nyimas Febrika Sya’baniah,; Icha Amelia, (International Journal of Integrated Engineering, 2025)
The implementation of Pd-Ni/C catalysts in PEMFCs is still quite limited, even though Pd and Ni alloys hold considerable promise as an alternative to decrease reliance on Pt/C. The PdNi/C metal alloy functions as a catalyst on the anode side for the hydrogen oxidation process in PEMFCs. The catalyst was synthesized by incorporating NiCl₂·6H₂O into Pd/C with a catalyst loading of 0.5 mg/cm². Electrodes were prepared with varying Pd to Ni weight ratios in carbon (3:1, 1:1, and 1:3), and were compared against Pd/C and Ni/C electrodes, while a Pt/C catalyst was used on the cathode side. The Membrane Electrode Assembly (MEA) was constructed by combining the anode containing the Pd-Ni/C catalyst, and the cathode containing the Pt/C catalyst using a Nafion 212 membrane. XRD characterization showed a carbon peak at 2θ = 26.4° and a palladium peak at 2θ = 41°, both with low intensity. XRD spectrum of Pd-Ni/C electrode showing amorphous crystal peaks. The highest catalytic activity of the electrode was achieved by the electrode with Pd:Ni = 3:1 with an ECSA value of 1.539 m²/g and conductivity value of 3.98 × 10-2 S/cm. The highest OCV value was obtained with the MEA using a Pd/C catalyst at ambient temperature, reaching 0.88 V, which was not significantly different from the 0.8 V value of the Pd:Ni= 3:1 catalyst. The maximum power density of MEA with Pd:Ni= 3:1 catalyst at the anode was 4.88 mW/cm² at a current density of 10 mA/cm². This research indicates that the MEA with the Pd:Ni = 3:1 catalyst at anode achieves optimal performance at an operating temperature of 25°C, contributing to high efficiency in PEMFC applications.